Pengelolaan Keuangan dengan menggunakan Aplikasi Buku Kas pada Jasa Penjahit Pakaian Rayon - Luh Putu Safitri Pratiwi; I Made Pasek Pradnyana Wijaya; Dedy Panji Agustino (Jurnal Pengabdian Masyarakat (abdira), 2022)
The business opportunity to sell clothes made of rayon is very promising, but in terms of financial management, partners who are engaged in a rayon tailoring service business located in Blahbatuh, Gianyar, Bali still record it manually in a book so that monthly financial reports still need to be calculated manually. manually. The purpose of this service activity is to solve the problems faced by partners by providing training using the BukuKas application in terms of financial management management, where the implementing team of this activity involves lecturers and students with areas of expertise that are in accordance with field needs. The method of activities carried out in this service is to conduct socialization and initial evaluation of the partner's condition, the preparation stage, the provision of materials and direct practice, and the final evaluation stage. The results of the training show that partners are able to use the BukuKas application as seen from the fulfillment of activity achievements above 50% in accordance with the initial design indicators expected by the service team.